AKIBAT HUKUM JIKA DEBITUR WANPRESTASI DALAM PEMBIAYAAN KONSUMEN DENGAN JAMINAN FIDUSIA PADA PT. MANDIRI TUNAS FINANCE - YESIKA PRATIWI SIDABOLOK (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Sunarmi, SH, MHum2.  Prof. Dr. Hasim Purba, SH, MHum'3.  Dr. Dedi Harianto, SH, MHum Consumer financing agreement contains a credit contract in which fund is given to a consumer as a debtor. It becomes a debt which has the same value as the fund, plus interest agreed by the parties. The research used juridical empirical and descriptive analytic method. The data were gathered by using library research and field research technique and conducting literature study, interviews, and documentary study. The result of the research shows that the defaults in consumer financing agreement at PT. Mandiri Tunas Finance was that debtors are not able to pay off their credit or are late in paying off their credit. A sanction will be imposed on a debtor who defaults by handing in a mortgage to creditor and paying off all debts, based on consumer financing agreement by executing fiduciary collateral according to Article 29 of Law No. 42/1999 on Fiduciary Collateral. Legal protection for a debtor can be given preventively and repressively. Preventive legal protection is done to save non-performing loan, and repressive legal protection is done to settle non-performing financing.Keywords: Legal Consequence, Debtor, Default, Consumer Financing